INITIATIVES TAKEN BY NCERT DIPLOMA HOLDERS TO PROMOTE ECCE IN THE STATES/UTS - CHANDRA, REETU (THE PRIMARY TEACHER, 2013)
Early Childhood Care and Education (ECCE) is an important aspect of school education. It is also a vital component for achieving universal enrolment and retention in primary schools. Therefore, it is essential to provide necessary maturational and experimental readiness to the children for meeting the demands of primary education curriculum. This readiness depends on child’s Early Care and Education, which includes health care, nutritional support and physical as well as psycho-social stimulation that can only be possible with the efforts of qualified and quality teachers in ECCE centres. Hence, it is important to give priority to capacity building of teachers and teacher trainers; building of resources in terms of teaching and instructional materials; provision for field experiences; funding and institutional support in the area of ECCE.